Post-Treatment Of Palm Oil Mill Effluent Using Modified Sequencing Batch Reactor Augmented With Zeolite - Farraji, Hossein (2018)
One of the biological treatment system for wastewater treatment is sequencing batch reactor (SBR). Post-treatment of palm oil mill effluent by direct application of municipal wastewater and augmentation of natural zeolite in aerobic modified SBR system. POME contain extremely high concentration of organic pollutants, very low concentration of toxic metallic elements, and low microbial content. Direct application of municipal wastewater as microbial supply and zeolite as natural coagulant in modified aerobic sequencing batch reactor (SBR) conducted in order to decreasing operation time and cost of operation process through the aerobic treatment. Aeration used for mixing and oxygen source in SBR system. Batch study carried out with 5, 10, 15, 20, 25, 30, and 35 g/L zeolite. 15g/L zeolite collected as optimum adsorbent dosage. The size of natural zeolite ranged from 75 μm to 150 μm. Response Surface Methodology (RSM) and Central Composite Design (CCD) were used for collecting the optimum operating conditions (independent variables) which were ratio of municipal wastewater (MWW) to POME, aeration flow and contact time. Seven parameters namely total suspended solids (TSS), biological oxygen demand (BOD5), chemical oxygen demand (COD), ammonia nitrogen (NH3-N), total nitrogen and total phosphorus selected as dependent parameters (responses). Collected results indicates that this single treatment method has capability for effective POME treatment in short time without requiring to sludge acclimatization process. In the optimum condition of municipal wastewater to POME ratio (58.7 v/v; %), aeration rate (6.85 L/min) and contact time (17.9h) for the SBR, efficiency of the reduction for TSS, BOD, COD, colour, ammonia nitrogen, total nitrogen and phosphorus were 99.16%, 90.67%, 98.4%, 84.34%, 98.33%, 96.26% and 93.49% respectively. Mechanism of removal mostly were microbial biodegradation, coagulation, cation exchangeable capacity, and surface adsorbent. Specific effect of municipal wastewater through the microbiological treatment process and assistance influence of zeolite for microbial growth and non-degradable maters coagulation are main aspects of efficiency. Combining municipal wastewater with POME and augmenting with natural zeolite in aerobic modified SBR system, could be considered as a capable microbiological method for POME in cost effective and short time treatment.